If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(c + 5) = -36 Reorder the terms: 6(5 + c) = -36 (5 * 6 + c * 6) = -36 (30 + 6c) = -36 Solving 30 + 6c = -36 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 6c = -36 + -30 Combine like terms: 30 + -30 = 0 0 + 6c = -36 + -30 6c = -36 + -30 Combine like terms: -36 + -30 = -66 6c = -66 Divide each side by '6'. c = -11 Simplifying c = -11
| 7m-3m=16 | | 3x+3(2x+11)=132 | | 9=b-2 | | 2.6=9.3/x | | 12=3+4b+5 | | 7/2-2/3= | | 9=xb-2 | | 5n+8(4n-3)=161 | | 137=7(3x+7)+x | | x^4+x^9=6 | | -14.2=-1.5k+3.2 | | x-4=10+8 | | -4.8p+2.2=17.56 | | 0.60x-1.05(150)=0.30(93) | | 6[3b-2]+5b=57 | | 27-11x=-3 | | -2y-22=5y+13 | | 7=×/5-1 | | 4[3x+2]=56 | | 7(5x+8)=(x-4) | | n/15-1=0 | | -7.3+x=8.7 | | 101.55-X=42.86 | | 4(2y+5)=5-3(y-5) | | 13-x=391 | | -7y-12=3y+8 | | -310=5n+7(-7n+6) 13 | | 5+[2x-1]=8 | | (2v+7)(1+v)=0 | | 9x-(3x+8)=7x-15 | | [8y+3]=21 | | [4n-12]=16 |